A comparison between consumer and industry perspectives on sustainable practices throughout the apparel product lifecycle. Issue 2 (4th May 2019) - Lou, Xingqiu; Cao, Huantian
ABSTRACT: Apparel companies have adopted different practices in the product lifecycle to reduce their environmental impact. The purpose of this study is to investigate consumers' purchase preference for the apparel industry's sustainable practices throughout the product lifecycle and to ascertain whether consumers are willing to pay a premium for products produced through these sustainable practices. The Brand Environmental Module of the Higg Index 2.0 was used as the benchmark of the industry's perspective on sustainable practices. An online survey was conducted to collect information about consumers' purchase preference of the industry's sustainable practices. It was found that consumers' purchase preference were not in line with the apparel industry's perspective throughout the apparel lifecycle, as well as within the stages of materials, manufacturing, and end of use. Furthermore, the consumers' willingness to pay a premium on the apparel industry's sustainable practices did not match the industry's perspective. This study recommends apparel companies to communicate and educate consumers regarding the industry's sustainable practices.